Emergency contraception practice and its related factors in a sample of Malaysian women. - Sharj Abad, Fatemeh Najafi (EuroJournals, 2011)
Emergency Contraception (EC) is a back-up method of contraceptive emergencies, which women can use within the first few days after unprotected intercourse to prevent an unintended pregnancy. In Malaysia, the use of modern contraceptive method is low whereby only 30% of married women used it. Studies have shown unwanted pregnancies among women are increasing. The aim of this study was to determine the usage rate of EC and its related factors among married female staff in University Putra Malaysia (UPM). A cross sectional study was conducted with using stratified random sampling from 15 faculties in UPM. The mean age of respondents was 35.8 Â± 9 years old. Mistimed pregnancy and unwanted pregnancy were reported by 35% and 13.6% of respondents respectively. The usage rate of EC was 11.2%. There was significant association between EC practice and type of abortion, advance prescription, EC counseling, practice regular contraception. Logistic regression for predictor variables showed positive attitude (OR=1.3, 95% CI=1.03-1.67) and counseling with health care providers (OR=0.09, 95% CI=0.009- 0.862) contributed significantly toward EC practice. Overall the usage rate of EC was low. Lack of knowledge of EC and fear of side effects were the most frequently reason for not using of EC. The present findings emphasize the importance positive attitude and counseling with health care providers in determining use of EC. Consideration should be taken when designed for educational activity programs or interventions.